PENINGKATKAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN BLENDED LEARNING MATERI LISTRIK DINAMIS - Mandang, Thresje; Tulandi, Djeli (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
Blended learning is a learning strategy that utilizes internet technology combined with face to face in class. The purpose of this study was to improve student learning outcomes in the material of Class XII Dynamic Electricity in SMA N 2 Tondano. This research is an experimental study with the design of the One Group Pretest-posttest design. The sample taken was Class XII IPA as an Experiment class with 22 students. Data is collected by conducting research observations and giving tests. The data were analyzed from the posttest results and from the process assessment students were in the good category 66% -79% and very good 80% -100%. In the normality test, researchers used the Liliefors test in Lcount = 0.162 while Ltable = 0.184 because Lcount <Ltable, then the data was normally distributed. Furthermore, hypothesis testing was done by t test at 5% significant level, obtained tcount = 5.215 while t table = 1.721 because tcount> ttable, so that it can be concluded that the Blended Learning learning model has an effect on student learning achievement.